PATIENTS WITH EPIRETINAL MEMBRANES DISPLAY RETROGRADE MACULOPATHY AFTER SURGICAL PEELING OF THE INTERNAL LIMITING MEMBRANE. Issue 11 (November 2019) - Dysli, Muriel; Ebneter, Andreas; Menke, Marcel N.; Zinkernagel, Martin; Wolf, Sebastian; Grabe, Hilary; Abegg, Mathias
Abstract : Purpose: Intraretinal cystoid spaces are commonly found after surgical peeling of epiretinal membranes. In this study, we explored whether these cysts were associated with ganglion cell loss and thus might be a manifestation of retrograde maculopathy. The latter is a nonvascular edema with a characteristic morphology that is often found in the inner nuclear layer (INL) of patients with optic neuropathy. Methods: In this retrospective case series, we identified consecutive patients who underwent surgical epiretinal membrane peeling. We determined the frequency of microcystic macular edema (MME), defined by vertical cystoid spaces in the INL, and we measured the thickness of individual macular layers before and after surgery. Results: Epiretinal membrane peeling resulted in an improvement of visual acuity and a reduction of retinal thickness by about 15%. In total, 35% of patients with MME before surgery showed no sign of MME postoperatively, whereas edema persisted after surgery in 65% of patients. Interestingly, 29% of the patients without MME before surgery developed MME after surgery. Overall, we found MME in 35% of patients before peeling and in 42% after peeling. After surgery, the mean ganglion cell layer thickness was reduced compared with healthy control eyes. Ganglion cell layer thickness correlated inversely with thickness of the INL. Compared with patients without MME, individuals with MME had a thinner ganglion cell layer and a thicker INL in the affected eye. Conclusion: Our findings indicate that peeling of epiretinal membranes and internal limiting membranes is associated with atrophy of ganglion cells and thickening of the INL. The latter is associated with the presence of MME. Altogether, we assume that surgical treatment of epiretinal membranes induces a variant of a retrograde maculopathy. Abstract : The authors show that surgical peeling of epiretinal membranes is associated with a signifi cant optic neuropathy and subsequent retrograde maculopathy. This mechanism may explain the high frequency of macular edema after surgery.